Using machine learning and agent-based simulation to predict learner progress for the South African high school education system - Van den Heever, Maymarie (Stellenbosch : Stellenbosch University, 2025)
Van den Heever, Maymarie. 2025. Using machine learning and agent-based simulation to predict learner progress for the South African high school education system. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131943